The Influence of Brand Image and Promotion On Product Purchasing Decisions at PT. Gaya Motor Branch Tarok Dipo Bukittinggi City - Mita Mita; Amsah Hendri Doni (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2023)
This study aims to determine and analyze the effect of brand image and promotion on product purchasing decisions at PT. Taxi Motorcycle Style. City of Tarok Dipo Bukittinggi. The type of research that the authors conducted was field research using a quantitative approach. The data used in this study were visitor data at PT. Style Motor Cab.Tarok Dipo Bukittinggi City 2017-2021 period (per year). This study used the SPSS (statistical package for social science) 26 program to process the data.   The results showed that partially brand image has a value of 0.00 less than 0.05 or (0.00 <0.05) thus it can be concluded that the brand image variable partially influences purchasing decisions, promotion is 0.868 greater than 0 .05 or (0.868 > 0.05) so that it can be concluded that the promotion variable does not affect the decision partially. Simultaneously brand image and promotion have F count > F table or 17.681 > 3.093. Thus it can be concluded that brand image and promotion have a significant effect on purchasing decisions.